Benzimidazole corrosion inhibition performance: A DFT Study - Farid Wajdi; Saprizal Hadisaputra; Iwan Sumarlan (Chemistry Education Program, the University of Mataram, 2018)
The corrosion inhibition performance of benzimidazole and its derivatives have been studied by density functional theory DFT in aqueous medium. For this investigation, the corrosion inhibition efficiencies of the protonated and non-protonated spesies of benzimidazole and its derivatives were investigated. The ionization potential of the inhibitors has a strong influence on the efficiency of corrosion inhibitors. The linear correlation was shown between electronic properties and corrosion inhibition efficiency. Electron donating substituents increase the corrosion inhibition efficiency, whereas electron withdrawing substituents give the opposite effect. The NH2 substituent contributes highest, whereas NO2 provides the weakest contribution to the corrosion inhibition efficiency for both non-protonated and protonated species of inhibitors.